Valuation methods and approaches for assessing natural resource management impacts - Shiferaw, B.; Freeman, H.A.; Navrud, S. (CAB International, 2005)
This chapter provides an overview of the valuation methods and methodological approaches used to evaluate the economic and environmental impacts of natural resource management (NRM) interventions. First, the multiple agro-ecosystem services associated with NRM are summarized. The core issues involved in the valuation of agro-ecosystem services are then discussed. This is followed by a presentation of the theoretical foundations of valuation methods along with some examples of applications in the area of natural resources. The next part summarizes how economic and environmental impacts can be integrated to provide an assessment of the social net benefits from NRM interventions, and the conclusion highlights the major issues and most promising valuation methods.